2002
DOI: 10.4049/jimmunol.168.4.1753
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dehydroepiandrosterone Restores Age-Associated Defects in the Protein Kinase C Signal Transduction Pathway and Related Functional Responses

Abstract: Elderly subjects are at increased risk of pneumonia, influenza, and tuberculosis. Besides the known age-related decrease in mechanisms for mechanical clearance of the lungs, impaired alveolar macrophage function contributes to the increased risk of illness in the elderly. We have previously shown that age-induced macrophage immunodeficiencies are associated with a defective system for anchoring protein kinase C. Castration of young male rats produces effects on alveolar macrophages similar to those of aging, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 29 publications
8
46
0
1
Order By: Relevance
“…Substantial data from animal studies have demonstrated a stimulatory effect of DHEA on immune function. We previously demonstrated in vitro and in vivo that DHEA can restore the age-related, defective TNF-␣ production in macrophages and mitogen-induced splenocyte proliferation [12]. May et al [23] demonstrated that DHEA administration reversed corticosteroid and stress-induced inhibition of immune function, Loria et al [24] showed that DHEA administration has a protective effect against systemic Coxsackie virus and Herpes simplex type 2 encephalitis, and Daynes et al [25] found that it can enhance IL-2 production by activated murine T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial data from animal studies have demonstrated a stimulatory effect of DHEA on immune function. We previously demonstrated in vitro and in vivo that DHEA can restore the age-related, defective TNF-␣ production in macrophages and mitogen-induced splenocyte proliferation [12]. May et al [23] demonstrated that DHEA administration reversed corticosteroid and stress-induced inhibition of immune function, Loria et al [24] showed that DHEA administration has a protective effect against systemic Coxsackie virus and Herpes simplex type 2 encephalitis, and Daynes et al [25] found that it can enhance IL-2 production by activated murine T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning aging of the immune system, we have shown that a deficit in RACK-1, in the absence of differences in the expression of total PKC isoforms, underlies defective PKC activation and functional immune impairment in aged rats [7,8]. Defective PKC activation with aging has also been reported by several authors in human monocytes [18,19] and in human T lymphocytes [20,21], and ϳ50% of elderly subjects has significant reduction in PKC activity in B cells [22].…”
Section: Introductionmentioning
confidence: 88%
“…We have recently demonstrated [7,8] that the age-associated decline in rat immune function reflects an impaired protein kinase C (PKC) signal-transduction pathway and in particular, is related to a defective PKC-anchoring system. PKC is a family of at least 12 phospholipid-dependent, serine-threonine kinases involved in the signal transduction of hormones, neurotransmitters, and cytokines [9].…”
Section: Introductionmentioning
confidence: 99%
“…57 Accordingly with this findings, this steroid restores RACK1 levels in aged rat alveolar macrophages and splenocytes. 58 Recently, in collaboration with Drs. Walter Pierpaoli and Daniele Bulian, we have obtained preliminary results on PKC activation in the brain of aged rats (25 months old) in which implantation of a pineal gland from young rats (3 months old) into the thymus was performed at 18 months.…”
Section: Interventions On Pkc Signal Transduction In Agingmentioning
confidence: 99%